Controle social e vigilância : o aparato repressivo e judicial na formação da cidade de Londrina - 1930/1955 - Ávila, Ingrid Carolina (2016)
This research analyzes the birth and action of the repressive apparatus of court in the city of Londrina (PR). The period was defined from 1934, date of Londrina´s foundation, to 1955, when it splits from the Sheriff's Department of the inner city. Police rises linked to the interests of the state in defense of the existing social structure in the Northern Paraná colonization process. However, analyzing criminal records and periodicals, it is noticed that there is an upheavel within the population due to the prohibitive measures to solve social conflicts, there are disparities between the formal design of the police apparatus and social reality. The people acted according to different rules, grounded in social situations established between the different segments. Thinking from the perspective of Michel Foucault, in this environment the power flows, we are faced with different social agents using strategies in an interdependence game, in a structured network of relations in which groups of political power hold an important role in shaping behavior